THE RELATIONS OF VAULT OF SKULL BONES WITH THE DURA MATTER OF BRAIN FOR ADULT HUMANS - Вовк О. Ю.; Ікрамов В. Б.; Шмаргальов А. О. (World of Medicine and Biology, 2014)
The article is devoted the study of morpho- and craniometric features of relations of vault of skull bones with the dura matter of brain for adult persons from position of individual anatomic variability.